Enhancement program of reciting al-Quran and fardhu ain through hybrid learning among orphans at Rumah Amal Baitul Kasih, Rawang = Program pemantapan bacaan al-Quran dan fardhu ain di kalangan anak-anak yatim melalui pembelajaran hybrid di Pusat Jagaan Anak-Anak Yatim Baitul Kasih Rawang - Sahrir, Muhammad Sabri; Ahmed Mahmoud, Ahmed Ragheb; Ahmad H.Osman, Rahmah; Zubir, Badri Najib; Mat Daud, Nuraihan; Nawi, Amani; Adzif, Azlilah; Ismail, Nur Shuhadak (2015)
This project involves the transfer of knowledge between the university community with a needy community of the orphans at Rumah Amal Baitul Kasih, Rawang. The project uses a hybrid learning that is a combination of traditional and computer-assisted in the enhancement program of Reciting al-Quran, Fardhu Ain and Arabic language. This KTP project is combining the theories of multimedia learning by Mayer (2001) and the hybrid learning by Nicole and Retta (2006) in the activities. Mayer (2001) states that " people learn more deeply from words and pictures than from words alone", while Nicole and Retta (2006) mentioned that the hybrid learning is effective in carrying 'in-depth learning' through the analysis of the knowledge provided to the students. The orphanage was chosen as the partner of this project because they are in dire need of love, strong support and an ongoing education to ensure that they are not left out of the current prime progress as part and parcel of nurturing process for future human capital for the nation. Teaching the Quran and Fardhu Ain is proposed in this pioneer project in building the human capital which has strong personality based on religious values that infuses manners and morals that control negative symptoms. (Islamic Education Syllabus, KBSM 2002). This paper presents some of conducted activities in the first quarter of 2014. In overall, this KTP project has successfully carried out with some modification on strategies and program dates due to some unavoidable constraints. Some children are found extremely weak in their skills of Jawi and Arabic, which require specific approaches to assist them during the learning activities. This project implies the need for the government to set up a special care centers for orphans under government supervision which integrate education and welfare in ensuring their future life.